Peran Strategis Tutor Dalam Meningkatkan Partisipasi Belajar Warga Belajar Paket B di SKB Kendal - Havid Ali Mahfud; Indri Ajeng Setyoningrum (Global Action and Education for Society, 2026)
This study aims to describe the role of tutors in improving the learning participation of students in the Package B equivalency program at the Kendal Regency SKB. The background of this study is the high dropout rate influenced by economic and social factors and low learning motivation. The method used was a descriptive qualitative approach through observation, interviews, and documentation with seven informants consisting of the head of the SKB, tutors, and learners. Tutors not only play a role in delivering material, but also in building interpersonal relationships, creating an inclusive learning atmosphere, and helping to overcome the emotional and social obstacles of participants. Supporting factors for participation include environmental support and positive interpersonal relationships, while inhibiting factors include workloads, economic conditions, and low self-confidence among participants. To increase learning participation, tutors need to function as facilitators, motivators, mediators, mentors, and evaluators, as these roles have been proven to have a significant effect on increasing the motivation, attendance, and independence of learners.